The Lorax [and] Pontoffel Pock and his magic piano - Pratt, Hawley; Freleng, Friz; Geisel, Ted; Universal Television Network; DePatie-Freleng productions (Universal City, Calif. : Universal Studio, 2003)
The Lorax tells the story of the greedy, tree-chopping Once-lers and the brave little Lorax who speaks up for the vanishing forest. Then, in Pontoffel Pock & His Magic Piano, a young Dill Pickle Works worker wishes he could get away from it all, and has his wish granted in a magically head-spinning, globe-trotting, song-singing way
Story 1. The Lorax (25 min.) - Story 2. Pontoffel Pock and His Magic Piano (25 min.)
Title from title screen
Also includes'Pontoffel Pock and His Magic Piano'
Executive producer, David H. DePatie ; music by Dean Elliot ; camera, John Burton, Larry Hogan, Ray Lee
Subtitles in French and English
Keywords: Animated films; Pollution -- Fiction; Pollution -- Juvenile films; Conservation of natural resources -- Fiction; Piano -- Fiction; Children's films